Measures for Self-Help Skills Education for 5–6-Year-Old Preschool Children Based on a Child-Centered Approach: Online First: 17/06/2026 - Pham Thi My Nu; Duong Thi Kim Oanh; Vo Phan Thu Huong (Journal of Technical Education Science, 2026)
Educating 5–6-year-old preschool children in self-help skills based on a child-centered approach provides them with opportunities to experience, explore, and practice these skills through participation in diverse daily activities that match their individual needs and interests. This article aims to propose measures for self-help skills education for 5–6-year-old preschool children based on the child-centered approach, in line with children’s developmental characteristics and the current requirements for innovation in preschool education. This article employs information gathering and document analysis methods to identify the characteristics of 5–6-year-old preschool children, the child-centered approach, self-help skills of 5–6-year-old preschool children and self-help skills education for this age group. The article also proposes five measures for educating self-help skills through a child-centered approach and illustrates their application in preschool educational practice. The findings contribute to establishing a scientific foundation for designing and implementing self-help skills educational activities for 5–6-year-old preschool children based on the child-centered approach in preschool institutions.